Uneven HAK/KUP/KT Protein Diversity Among Angiosperms: Species Distribution and Perspectives - Nieves-Cordones, Manuel; Ródenas, Reyes; Chavanieu, Alain; Rivero, Rosa M.; Martinez, Vicente; Gaillard, Isabelle; Rubio, Francisco (Frontiers in Plant Science, 2016)
HAK/KUP/KT K+ transporters have been widely associated with K+ transport across membranes in bacteria, fungi and plants. Indeed some members of the plant HAK/KUP/KT family contribute to root K+ uptake, notably at low external concentrations. Besides such role in acquisition, several studies carried out in Arabidopsis have shown that other members are also involved in developmental processes. With the publication of new plant genomes, a growing interest on plant species other than Arabidopsis has become evident. In order to understand HAK/KUP/KT diversity in these new plant genomes, we discuss the evolutionary trends of 913 HAK/KUP/KT sequences identified in 46 genomes revealing five major groups with an uneven distribution among angiosperms, notably between dicotyledonous and monocotyledonous species. This information evidenced the richness of crop genomes in HAK/KUP/KT transporters and supports their study for unraveling novel physiological roles of such transporters in plants.